1996
DOI: 10.1096/fasebj.10.8.8666165
|View full text |Cite
|
Sign up to set email alerts
|

Neurohormone melatonin prevents cell damage: effect on gene expression for antioxidant enzymes

Abstract: It is well known that porphyrins cause a toxic light-mediated effect due to their capability to generate free radicals. Several reports have proved that melatonin is a potent free radical scavenger. The aim of this work has been to study the ability of melatonin to prevent the cell damage caused by porphyrins in the Harderian gland of female Syrian hamsters. Cell injury was evaluated estimating the percentage of damaged cells found in the gland and analyzing the degree of this damage at ultrastructural level. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
287
2
4

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 446 publications
(314 citation statements)
references
References 5 publications
19
287
2
4
Order By: Relevance
“…Melatonin displays important antioxidant properties based on its free radical scavenger ability [46,48,52,53] and, in contrast to conventional antioxidants, rapidly crosses the blood-brain barrier after systemic administration and reaches every neuronal compartment [41]. Melatonin also regulates the expression and activity of the redox enzymes [9,16]. Deprenyl shares with melatonin common features such as neuroprotective and antioxidant effects, and we recently reported a synergistic effects between both compounds against DA autoxidation in vitro [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin displays important antioxidant properties based on its free radical scavenger ability [46,48,52,53] and, in contrast to conventional antioxidants, rapidly crosses the blood-brain barrier after systemic administration and reaches every neuronal compartment [41]. Melatonin also regulates the expression and activity of the redox enzymes [9,16]. Deprenyl shares with melatonin common features such as neuroprotective and antioxidant effects, and we recently reported a synergistic effects between both compounds against DA autoxidation in vitro [32].…”
Section: Discussionmentioning
confidence: 99%
“…Other actions of deprenyl such as the increase in superoxide dismutase activity [34], the reduction of free radical formation [32], and the antiapoptotic activity [55], are also involved in its neuroprotective effect. Melatonin is a strong scavenger of free radicals [46,48] and regulates the activity and expression of antioxidant enzymes [9,37]. Melatonin reportedly protects cells, tissues and organs against oxidative damage caused by various free radical generating agents [5,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…However, aMT mainly reduces NO• through the inhibition of its synthesizing enzyme, nitric oxide synthase NOS (Escames et al, 2003). In addition to these scavenging action, aMT also stimulates several antioxidative enzymes including SOD, and glutathione peroxidase (GPx) and reductase (GPx); these actions further reduce the oxidation state in the majority of cells (Antolin et al, 1996;Barlow-Walden et al, 1995;Okatani et al, 2000;Pablos, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that acute aMT administration, an antioxidant and free radical scavenger (Antolin et al, 1996;Tan et al, 2000aTan et al, , 2000bTan et al, , 2002Turjanski et al, 2001), counteracted mitochondrial deficiencies in SAM mice (Okatani et al, 2001(Okatani et al, , 2002a(Okatani et al, , 2002b. The indoleamine and several of its metabolites are scavengers of free radicals and it is now considered a component of the endogenous antioxidant system (Reiter, 1998(Reiter, , 2000Tan et a., 2007).…”
mentioning
confidence: 99%
“…5 Additional protective effects of melatonin may lie within the ability of this hormone to reduce oxyradical-related oxidant processes by either directly interfering with the oxidants or up-regulating antioxidant systems, such as superoxide dismutase or enhancing the catalytic activity of glutathione peroxidase. 10 Melatonin has also been proposed as an antiapoptotic agent, as it readily penetrates the blood-brain barrier and diffuses into neurons and glia equally well. 3,7,11 SCI induces many types of physiological and pathological damage including variations in various hormonal levels.…”
Section: Introductionmentioning
confidence: 99%